Antigravity, an Answer to Nature’s Phenomena including the Expansion of the Universe - C. K. Gamini Piyadasa (Advances in High Energy Physics)
The gravitational attraction force being proportional to the mass has been experimentally shown for several hundred years now, but no gravitational repulsion has been identified within the accepted scientific reasoning. Here, we show that the gravitational repulsion force, similar to the gravitational attraction among particles has also been in existence in nature but, yet to be recognized. The results of experiments are shown in detail and are discussed in the recent series of-publications. It is also shown here that this gravitational repulsion force is proportional to the temperature which is an indicator of thermal energy of the particle, similar to the gravitational attraction that is proportional to the mass of the particle. The situations where heavy particles such as iodine, tungsten, and thorium in vacuum move against gravitational force have already been shown qualitatively. The increase in time-of-fall of water droplets (slowing down of fall) with rise in temperature is also quantitatively discussed. This article discusses two major phenomena observable in nature, clouds and the expansion of universe, which could be more preciously explained by the concept of antigravity.